Risk factors associated with postoperative respiratory failure after esophagectomy for esophageal cancer - Zhanglan Fang; Hao Yang; Yi Long; Dongyun Xu; Benyu Su; Chao Xu; Huguang Yang; Feng Xu; Ling Luo (Open Exploration Publishing Inc., 2023)
Aim: Respiratory failure is common after esophagectomy for esophageal cancer (EC). This study aimed to identify the risk factors associated with postoperative respiratory failure following esophagectomy for EC. Methods: A single-center observational study from China was conducted on 262 patients with EC who underwent thoracoscopic esophagectomy between April 2014 and June 2016. The patients were divided into two groups: group I (respiratory failure) and group II (without respiratory failure). Demographic and perioperative variables, tumor-related factors, surgical factors, Acute Physiology and Chronic Health Evaluation II (APACHE II) scores, and clinical course were compared between the groups. Univariable and multivariable logistic regression analyses were performed to assess the risk factors of postoperative respiratory failure after esophagectomy. Results: Among the 262 patients, 24 (9.2%) developed respiratory failure. Univariable analysis revealed several risk factors, including age, smoking, comorbidities, partial pressure of oxygen (PO2), partial pressure of carbon dioxide (PCO2), forced vital capacity (FVC), FVC percentage (FVC%), urine volume during surgery, and APACHE II score. Multivariable analysis showed that age, comorbidities of diabetes mellitus (DM), FVC%, urine volume during surgery, and APACHE II score were independent predictors of respiratory failure. Specifically, elderly patients (> 65 years) with comorbidities of DM, lower FVC%, higher urine volume during surgery, and elevated APACHE II score were found to be more susceptible to respiratory failure, resulting in prolonged hospitalization and increased healthcare burden. These findings emphasize the importance of considering these factors in the management and care of patients at risk of respiratory failure. Conclusions: As a common complication following esophagectomy for EC. Respiratory failure is significantly associated with age, comorbidities of DM, FVC%, urine volume during surgery, and APACHE II score in the dataset. The findings will contribute to the evaluation of the risk of respiratory failure and guide early intervention strategies in clinical decision-making.